A Human Study to Evaluate Safety, Tolerability, and Cyclic GMP Activating Properties of Cenderitide in Subjects With Stable Chronic Heart Failure. Issue 3 (11th January 2018) - Kawakami, Rika; Lee, Candace Y.W.; Scott, Christopher; Bailey, Kent R.; Schirger, John A.; Chen, Horng H.; Benike, Sherry L.; Cannone, Valentina; Martin, Fernando L.; Sangaralingham, S. Jeson; Ichiki, Tomoko; Burnett, John C.
Abstract : Cenderitide is a novel designer natriuretic peptide (NP) composed of C‐type natriuretic peptide (CNP) fused to the C‐terminus of Dendroaspis natriuretic peptide (DNP). Cenderitide was engineered to coactivate the two NP receptors, particulate guanylyl cyclase (pGC)‐A and ‐B. The rationale for its design was to achieve the renal‐enhancing and antifibrotic properties of dual receptor activation, but without clinically significant hypotension. Here we report the first clinical trial on the safety, tolerability, and cyclic guanosine monophosphate (cGMP) activating properties of Cenderitide in subjects with stable heart failure (HF). Four‐hour infusion of Cenderitide was safe, well‐tolerated, and significantly increased plasma cGMP levels and urinary cGMP excretion without adverse effects with no change in blood pressure. Thus, Cenderitide has a favorable safety profile and expected pharmacological effects in stable human HF. Our results support further investigations of Cenderitide in HF as a potential future cGMP‐enhancing therapeutic strategy.